2017
DOI: 10.1111/bjd.15363
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 family cytokines pathway: genetic variants and psoriasis

Abstract: This study presents a novel finding that the combination of the two SNPs, IL10 (rs1554286) and IL20 (rs1518108), is associated with a reduced risk of psoriasis. Our results indicate that genetic variants of the immunomodulatory IL10 and IL20 genes may offer a protective effect in Europeans from Russia. Independent studies are required to verify the results and find a possible functional explanation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 63 publications
(162 reference statements)
0
8
0
Order By: Relevance
“…In African Americans, the rs1400986 and rs1518108 polymorphisms were associated with chronic hepatitis B infection [16]. Galimova et al, [30] analyzed 48 polymorphisms in 377 patients with psoriasis and 403 healthy controls and reported that the rs1400986 T allele was associated with decreased risk of psoriasis and that the combination of IL10 rs1554286 and IL20 rs1518108 was associated also with a reduced risk of presenting this disease. In these studies, were only compared the three different genotypes in each polymorphism, they did not use an analysis considering the inheritance models like in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In African Americans, the rs1400986 and rs1518108 polymorphisms were associated with chronic hepatitis B infection [16]. Galimova et al, [30] analyzed 48 polymorphisms in 377 patients with psoriasis and 403 healthy controls and reported that the rs1400986 T allele was associated with decreased risk of psoriasis and that the combination of IL10 rs1554286 and IL20 rs1518108 was associated also with a reduced risk of presenting this disease. In these studies, were only compared the three different genotypes in each polymorphism, they did not use an analysis considering the inheritance models like in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuated expression of Mda-7/IL-24 was found in various kinds of carcinomas, such as colon cancer, breast cancer, melanoma and acute myeloid leukaemia [4,16,17]. The decreased expression of Mda-7/IL-24 was thought to be associated with numerous tumour biological characteristics, such as growth, metastasis, recurrence and chemotherapy resistance [4,[18][19][20]. Our previous studies have shown that transfection of endogenous Mda-7/IL-24 induced mature differentiation of Raji and Daudi lymphoma cells, which was Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuated expression of Mda-7/IL-24 was found in acute myeloid leukemia and Burkitt lymphoma cells ( 3 , 4 , 15 ). The decreased expression of Mda-7/IL-24 was thought to be associated with numerous tumor biological characteristics, such as differentiation blockage, malignant proliferation, invasion and chemotherapy resistance ( 4 , 16 18 ). Our previous studies have shown that transfection of endogenous Mda-7/IL-24 induced terminal differentiation of Burkitt lymphoma cells, which was characterized by growth inhibition, morphological and cell surface antigens changes and decreased expression of malignant markers ( 7 ).…”
Section: Discussionmentioning
confidence: 99%